Can We Predict and Prevent Subclinical Depression in Adolescents?. Issue 2 (February 2018) - Miloseva, Lence; Vukosavljevic-Gvozden, Tatjana; Milosev, Vladimir; Davis, Thompson
Abstract : Abstract: The purposes of this article were to determine which risk factors are significant predictors of the occurrence of depression in adolescence and to discriminate among clinical, subclinical, and control groups. The sample consisted of 412 adolescents (61.7% female, 38.3% male) aged 13 to 17 years. Cognitive vulnerability factors for depression ( i.e., dysfunctional attitudes, negative inferential style, ruminative response style) and psychosocial risk factors ( i.e., negative life events, perceived social support) were measured. Subsequent discriminant function analysis indicated that it was possible to distinguish groups on the basis of the mentioned predictors, and it allocated two discriminant functions (significant at p < 0.001). Unexpectedly, ruminative response style was the most powerful discriminative predictor possessing a positive and adaptive part, and, at the same time, it maximally distinguished the subclinical group from the clinical and control groups.